Outcomes With Age Combinations in Living Donor Kidney Transplantation. Issue 6 (June 2020) - Aslam, Sadaf; Buggs, Jacentha; Wasserman, Jacob; Chaves, Kendall; Rogers, Ebonie; Kumar, Ambuj; Huang, James
Introduction: Reevaluation of donor criteria, including age, is needed to combat organ shortages, lengthy wait times, and anticipated recipient mortality rates. The purpose of this study was to evaluate donor and recipient (D/R) age combinations and patient and graft survival outcomes. Methods: Single-organ, living donor kidney transplantations (LDKTs) from 2012 to 2018 were retrospectively reviewed. Donors and recipients were placed into "older" and "younger" age categories of 50 years and above or below age 50, then analyzed with SPSS version 25. Results: We performed 347 LDKTs. Younger-to-older pairings had significantly higher rates of smoking in recipient (53.6%) and hepatitis C (5.5%), but shorter hospital stays (5.3 days). Older-to-younger pairings had the longest hospital stays (7.4 days) but the shortest cold ischemic time (2.3 hours). Notably, there was no significant variance in delayed graft function (first-week dialysis) between groups. Regarding complication rates, only bleeding within 30 days, highest in older-to-older pairings (7.7%), and renal complications, highest in older-to-younger pairings, significantly varied between groups. Interestingly, though younger-to-older cases had the longest mean graft survival time, older kidneys lasted 537 days longer in older recipients than in younger recipients. Discussion: These results indicate there is not a one-size-fits-all approach when considering outcomes of donor/recipient age-pairings in LDKT, as significant correlations did not consistently favor one age-pairing over others. Regardless of age-pairing, LDKT provides gold standard treatment and expands the availability of organs. Future research into the impact of age-pairing on specific variables, national or multicenter studies, and protocol development for evaluating donor/recipient age-pairings is needed.